2018
DOI: 10.1088/1361-6463/aaee04
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of molten pool during selective laser melting of Ti–6Al–4V

Abstract: The characteristics of molten pools provide valuable insight into the complexity of the metal additive manufacturing process, which has a significant influence on the quality of the parts built using this process. In our work, we develop a three-dimensional multiphysics finite element model of a selective laser melting (SLM) process on a Ti-6Al-4V alloy. The dynamic characteristics of the molten pool are studied by multiphysics simulation with consideration of phase transitions, recoil pressure, surface tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…The process parameters influence the phases, recoil pressure, surface tension, Marangoni effect, and hydrodynamics that affects the size, and shape of the melt pool. When the laser beam leaves the melt area, the melt pool starts to cool down and solidifies [58,59]. As such the creation of a stable melt pool with a regular shape and geometrical characteristics, the powder characteristics of Co-Cr-Mo and laser processing parameters are the significant factors.…”
Section: Laser Powermentioning
confidence: 99%
“…The process parameters influence the phases, recoil pressure, surface tension, Marangoni effect, and hydrodynamics that affects the size, and shape of the melt pool. When the laser beam leaves the melt area, the melt pool starts to cool down and solidifies [58,59]. As such the creation of a stable melt pool with a regular shape and geometrical characteristics, the powder characteristics of Co-Cr-Mo and laser processing parameters are the significant factors.…”
Section: Laser Powermentioning
confidence: 99%
“…They found that in addition to process parameters, thermal [59]. (e) Schematics of melt pool simulation [54].…”
Section: Melt Pool Formation Simulationmentioning
confidence: 99%
“…In most cases, many simplifying assumptions were necessary to reduce the computational cost or to enable the application of the models. For instance, the powder bed was often assumed as a homogeneous and continuous material layer (Zhang et al, 2018), or as a homogenized porous (partly solid, partly gaseous) layer (Heeling et al, 2017). Highly sophisticated simulations that represent individual powder particles, as done by Khairallah et al (2016), Chen et al (2020) and Qiu et al (2015), on the other hand, are too costly for extensive studies that would provide relations between process parameters and MP formation for a wide range of parameters.…”
Section: Introductionmentioning
confidence: 99%